Stepwise synthesis of 2, 6-difunctionalized ethyl pyrazolo[1, 5-a]pyrimidine-3-carboxylate via site-selective cross-coupling reactions: experimental and computational studies. Issue 48 (23rd November 2022) - Messaoudi, Chaima; Jismy, Badr; Jacquemin, Johan; Allouchi, Hassan; M'Rabet, Hédi; Abarbri, Mohamed
Abstract : A variety of novel disubstituted 2-(alknyl, aryl and arylamine)-6-alkynylpyrazolo[1, 5- a ]pyrimidine derivatives was prepared via sequential site-selective cross-coupling reactions from 2, 6-dibromopyrazolo[1, 5- a ]pyrimidine 3 . Abstract : A variety of novel disubstituted 2-(alknyl, aryl and arylamine)-6-alkynylpyrazolo[1, 5- a ]pyrimidine derivatives was prepared via sequential site-selective cross-coupling reactions from 2, 6-dibromopyrazolo[1, 5- a ]pyrimidine 3 . The regio-controlled Sonogashira-type coupling of 3 with a wide range of terminal alkynes proceeded smoothly with excellent selectivity in favor of the C6-position through careful adjustment of the coupling conditions, followed by the subsequent introduction of alkynyl, aryl or arylamine groups at the C2-position via the Sonogashira, Suzuki–Miyaura and Buchwald–Hartwig coupling reactions, respectively. These promising results allow for further use and diversification of the chemically and biologically interesting pyrazolo[1, 5- a ]pyrimidine scaffold. In addition, computational studies were conducted to provide explanations for the origin of regioselectivity.